Location of the Low Temperature Water Flow Barrier in Stems - Molz, Fred J. (1974)
Experiments are described indicating the magnitude and location of the low temperature barrier to lateral water flow in stems of cotton (Gossypium hirsutum L. `Auburn 7-683'). Rehydration of wilted stem tissues was performed at 6 C and 32 C. Compared with the 32 C control, a 13-fold increase in the rehydration halftime was recorded at 6 C when water entered the secondary phloem tissues across the vascular cambium from the secondary xylem. However, only a 3-fold increase in the rehydration halftime occurred when water entered phloem tissues through the cortex, and most of this increase was due to the higher viscosity of water at the lower temperature. These results show that the cambial region of an intact cotton stem markedly resists the radial flow of water at lower temperatures. This resistance was not demonstated by other stem tissues.